Hairy roots: An untapped potential for production of plant products - Morey, Kevin J.; Peebles, Christie A. M. (Frontiers in Plant Science, 2022)
While plants are an abundant source of valuable natural products, it is often challenging to produce those products for commercial application. Often organic synthesis is too expensive for a viable commercial product and the biosynthetic pathways are often so complex that transferring them to a microorganism is not trivial or feasible. For plants not suited to agricultural production of natural products, hairy root cultures offer an attractive option for a production platform which offers genetic and biochemical stability, fast growth, and a hormone free culture media. Advances in metabolic engineering and synthetic biology tools to engineer hairy roots along with bioreactor technology is to a point where commercial application of the technology will soon be realized. We discuss different applications of hairy roots. We also use a case study of the advancements in understanding of the terpenoid indole alkaloid pathway in Catharanthus roseus hairy roots to illustrate the advancements and challenges in pathway discovery and in pathway engineering.